Bacterial and yeast optimization in Arabica coffee fermentation to enhance winey flavor - INTAN TAUFIK; FATHYA ISTIQOMARIL SYACHNOORMALIETA; KHAERUNISSA ANBAR ISTIADI; FAUZIE FITRIA RUSDIANA; DEA INDRIANI ASTUTI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Taufik I, Syachnoormalieta FI, Istiadi KA, Rusdiana FF, Astuti DI. 2024. Bacterial and yeast optimization in Arabica coffee fermentation to enhance winey flavor. Biodiversitas 25: 4265-4274. The natural fermentation process of Arabica coffee often needs more consistency in producing high-quality coffee due to the process's challenging control involving diverse microbial communities, including those of bacteria and yeast. This study has isolated specific bacteria and yeast strains from natural fermentation and utilized them as inoculum to optimize the coffee fermentation process, accentuating the wine's aromatic flavors by adjusting the bacteria-to-yeast ratio and inoculum percentage. Eight bacteria and five yeast were initially isolated from natural fermentation processes and further assayed for their enzymatic activity. The highest enzymatic activity, including pectinolytic, cellulolytic, amylolytic, and proteolytic activities from each bacterial and yeast, were selected for identification using DNA sequencing and phylogenetic tree construction. The identification results showed that the bacteria Klebsiella sp. and the yeast were Pichia kudriavzevii. Next, the growth curves of the two isolates were analyzed to determine the optimal fermentation time. The results indicated that one day was sufficient for optimal bacterial and yeast growth. Using the isolates bacteria Klebsiella sp. and yeast Pichia kudriavzevii revealed that a bacteria-to-yeast ratio of 1:10 with a 15% (v/w) inoculum resulted in the highest cupping score with a prominent wine flavor note compared to the control. Employing bacterial and yeast inoculum in Arabica coffee fermentation has the potential to improve coffee quality and consistently improve overall product standards.